Antifungal efficacy of four plant-derived essential oils against Botrytis cinerea: chemical profiles and biological activities - Faical AOUJIL; Loubna DRA; Chaimae EL GHDAICH; Sarah TOUFIQ; Hiba YAHYAOUI; Majida HAFIDI; Aziz AZIZ; Khaoula HABBADI (Phytopathologia Mediterranea, 2025)
Chemical compositions and the antifungal efficacy of essential oils derived from Origanum elongatum, Mentha pulegium, Thymus vulgaris, or Corymbia citriodora were assessed against the grapevine gray mold pathogen Botrytis cinerea, isolated from Moroccan vineyards. Gas chromatography-mass spectrometry (GC-MS) analyses identified the major constituents of these oils as carvacrol (61.8%) from O. elongatum, pulegone (91.2%) from M. pulegium, thymol (47.8%) from T. vulgaris, and cineol (78.11%) from C. citriodora. All these essential oils had antifungal activity, inhibiting in vitro colony radial growth and conidium germination of B. cinerea. Among the essential oils, that from O. elongatum exhibited the greatest inhibition of mycelium growth, with minimum inhibitory concentrations (MICs) and effective concentrations (EC50), respectively, of 252.5 µL L-1 and 33.27 µL L-1 in direct contact, and 56.17 µL L-1 and 12.75 µL L-1 in fumigation. At 125 µL L-1, origanum essential oil completely inhibited B. cinerea conidium germination. In vivo tests with detached leaves of two grapevine cultivars and grape berries showed that essential oils from M. pulegium and O. elongatum reduced the lesion diameters by, respectively, 78% and 72% on the leaves, and by 58% and 50% on grape berries. The results indicate the potential of using these essential oils as natural and effective alternatives to chemical fungicides for control of B. cinerea, offering a promising strategy for sustainable and environmentally friendly disease management practices.